Comparison of performance characteristics between high‐performance liquid chromatography and latex agglutination turbidimetric immunoassay for therapeutic drug monitoring of zonisamide. Issue 7 (20th June 2019) - Eto, Daiki; Tanaka, Ryota; Suzuki, Yosuke; Sato, Yuhki; Itoh, Hiroki
Abstract: Background: Recently, the Nanopia ® TDM Zonisamide reagent using the latex particle‐enhanced turbidimetric immunoassay (LTIA) method was developed. The aim of this study was to compare the differences in serum zonisamide (ZNS) concentrations quantified by the high‐performance liquid chromatography (HPLC) method and the LTIA method using a TBA‐25FR analyzer. Methods: A total of 78 samples from 33 patients were quantified by both HPLC and LTIA methods. Deproteinization was used as pretreatment for the HPLC method. The ZNS concentrations quantified by two methods were compared. Results: The HPLC method had intra‐ and inter‐day precision lower than 1.86% and 9.00%, and accuracy better than 2.44% and 6.33%, respectively. The LTIA method showed intra‐ and inter‐day precision lower than 2.50% and 5.20%, and accuracy better than 15.80% and 10.60%, respectively. The lower limits of quantification for the HPLC and LTIA methods were 1.0 and 5.0 µg/mL, respectively. The ZNS concentration quantified by the HPLC method correlated strongly with that by the LTIA method ( r  = 0.953, P  < 0.001). A Bland‐Altman plot suggested no systematic error between ZNS concentrations quantified by HPLC and LTIA methods. Conclusion: This study confirmed no differences between the concentrations quantified by the HPLC and LTIA methods at both high and low concentrations, demonstrating the confidence of measurement by the LTIA method.